Clinical Impact of Nurses-Physicians Collaboration Intervention on the Treatment of Immune Recurrent Spontaneous Abortion with Low-Molecular-Weight Heparin - Miaocheng Chen (Hindawi Limited, 2021)
Anticoagulation is currently the preferred and effective treatment for patients with recurrent spontaneous abortion (RSA), but, due to the prevalence of mood disorders in RSA patients and the high number of adverse effects associated with long-term medication, effective care measures are often required. In this study, 94 patients with immune-type RSA who were admitted to our hospital from January 2018 to June 2019 were selected and randomly divided into a control group and a study group of 47 patients each; both groups received low-molecular-weight heparin treatment after admission, and the control group received conventional nursing interventions during treatment, while the patients in the study group received integrated medical and nursing care interventions. Pregnancy outcomes, pre- and postintervention scores on the Self-Assessment Scale (SAS), Self-Depression Scale (SDS), and Pittsburgh Sleep Quality Index (PSQI), levels of serum gamma-interferon (IFN-γ) and interleukin-4 (IL-4) and their ratios, complications, and patient satisfaction with the intervention were observed in both groups. The results showed that the success rate of fetal preservation in the study group (89.36%) was significantly higher than that in the control group (68.09%) (P<0.05). After treatment, SAS, SDS, and PSQI scores decreased in both groups, with the study group being lower (P<0.05). IFN-γ and IFN-γ/IL-4 levels decreased and IL-4 levels increased in both groups after treatment, with IFN-γ and IFN-γ/IL-4 being significantly lower and IL-4 levels being significantly higher in the study group than in the control group (P<0.05). The incidence of adverse drug reactions in the study group was significantly lower than that in the control group (P<0.05). Patients in the study group were more satisfied with all aspects of the intervention than the control group (P<0.05). These results suggest that nurses-physicians collaboration intervention may improve the effectiveness of low-molecular-weight heparin therapy in patients with immune-type RSA. It helps to improve patient pregnancy outcomes, mood, sleep quality, and immune function and increases patient satisfaction.